The Development of Civil Society in Indonesia and the Role of Voluntary Organizations (American Journal of Islam and Society, 2000)
This article describes the evolution of Indonesia's voluntary sector andthe role of nongovernmental and private voluntary organizations in thedevelopment of Indonesia's civil society. The paper describes howNGOs and PYOs complement and supplement the role of governmentin the social and economic development of the society. It also discusseshow these organizations manage their responsibility in challengingthe government while often remaining financially dependent on thegovernment for their existence. The paper also advances discussionsabout the organizational theory of voluntary organizations and theirparticular development in Indonesia.